Aplicación web para la gestión de productos farmacéuticos e insumos médicos de la empresa “COFARMO Distribuciones”. - Pibaque Vera, Byron Enmanuel (2020)
This technological proposal project consists of developing a web application focused on the requirements of the company Cofarmo Distribuciones dedicated to the distribution of generic drugs, medical devices, hospital supplies, which will allow better inventory control, better management of productive information, saving of invoicing time and therefore dispatch of the products that are sold showing the real number of Stock that you have. The web application will be based on Asp.Net and its programming language in C #, connected to a Database created in SQL Server where all the data regarding the company and production management are recorded. The system in turn will automate various processes that will allow an improvement in productive business development.